The factors causing computers to fall victims to online shopping scams - Felice, Fong; Abu Bakar, Elistina (Persatuan Ekonomi Pengguna Dan Keluarga Malaysia, 2022)
This study aimed to identify the factors that contribute to the behaviours of potential victims of online shopping scams. One hundred fifty respondents who participated in this study were chosen using the multistage random sampling method. Data were collected using a set of questionnaires to identify threat awareness, technological advancement, negative emotions, and consumers' online behaviours. The self-control theory was adopted to explain the behaviours of consumers and their factors. The findings showed a significant relationship between all three independent variables (threat awareness, technological advancement, and negative emotion) with the dependent variable (the behaviour of online shopping scam victims). The findings from this study would help the consumer groups or government increase the awareness among online shopping consumers so that they will not fall for scams easily. Other than that, by knowing the factors contributing to the behaviours of potential victims of online shopping scams, consumers will be more alert and will not perform impulsive purchasing without further consideration.